2020
DOI: 10.1002/fsn3.1740
|View full text |Cite
|
Sign up to set email alerts
|

Severity of subjective forgetfulness is associated with high dietary intake of copper in Japanese senior women: A cross‐sectional study

Abstract: This study investigated the relationship between subjective forgetfulness and the dietary intake of various nutrients in middle‐aged and senior women. A cross‐sectional study of the first‐visit records of 245 Japanese women aged 40 or over was performed. The severity of subjective forgetfulness was classified according to the Menopausal Health‐Related Quality of Life Questionnaire: none and mild (“unforgetful”) or moderate and severe (“forgetful”). Dietary consumption of nutrients was estimated using the brief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…After CQ treatment, deposition of Cu + in the cell was markedly decreased ( Figure 2 ). In an epidemiological study, high dietary intake of copper in elderly Japanese women was associated with the severity of subjective forgetfulness [ 40 ]. PHF-1, CP13, AT180, and AT270-positive phosphorylated tau decreased, suggesting that phosphorylation of tau was suppressed at Ser394/404, Thr231, Thr181, Thr205, and Ser202.…”
Section: Discussionmentioning
confidence: 99%
“…After CQ treatment, deposition of Cu + in the cell was markedly decreased ( Figure 2 ). In an epidemiological study, high dietary intake of copper in elderly Japanese women was associated with the severity of subjective forgetfulness [ 40 ]. PHF-1, CP13, AT180, and AT270-positive phosphorylated tau decreased, suggesting that phosphorylation of tau was suppressed at Ser394/404, Thr231, Thr181, Thr205, and Ser202.…”
Section: Discussionmentioning
confidence: 99%
“…All participants in the program visited or were referred to our clinic for the treatment of menopausal symptoms. Of these, 494 responded to the Menopausal Health-Related Quality of Life Questionnaire (MHR-QOL) [ 7 ] and the brief-type self-administered dietary history questionnaire (BDHQ) [ 8 , 9 ]. The 46 patients treated with hormone replacement therapy, 35 patients younger than 40 years or older than 59 years, and 4 patients with unknown menopausal status were excluded, leaving 409 patient records included for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The MHR-QOL, developed and validated in our clinic [ 7 ], is a modification of the Women’s Health Questionnaire and other questionnaires [ 10 , 11 , 12 ]. Physical and psychological symptoms were scored on a 4-point Likert scale based on the frequency of symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Li et al reported that excessive copper intake could increase ceruloplasmin and raise oxidative stress, which led to a lowering of cognitive performance [37]. It was reported that high dietary copper intake (10 mg/kJ) would increase forgetfulness by 1.25-fold in elderly women [38]. A previous prospective study showed that a high calcium and vitamin D intake (1200 mg/day and 800 IU/day) resulted in better cognitive performance than the low-dosage group (600 mg/day and 400 IU/day) [39].…”
Section: Nutrients and Cognitive Impairmentmentioning
confidence: 99%